A Win for the Private Sector : Harmonizing Standards in the East African Community Partner States - Nderitu, Elizabeth Murugi; Odongo, Mary (International Finance Corporation, Washington, DC, 2017)
Trade Mark East Africa (TMEA) launched its standards harmonization project in 2011 to help businesses cut costs associated with the different standards in force across the East African community (EAC). The first phase of the project will come to an end in June 2017. This project stemmed from the importance of standards development for regional integration and has been done through supporting the national bureaus of standards in achieving regional harmonization. Product standards have a significant impact on trade in goods within the EAC while non-harmonized standards continue to interrupt the smooth flow of goods in the region. This smart lessons describe the challenges to the harmonization process and how the project’s successful implementation is boosting trade within the region.